Feasibility of monitoring advanced melanoma patients using cell‐free DNA from plasma - Gangadhar, Tara C.; Savitch, Samantha L.; Yee, Stephanie S.; Xu, Wei; Huang, Alexander C.; Harmon, Shannon; Lieberman, David B.; Soucier, Devon; Fan, Ryan; Black, Taylor A.; Morrissette, Jennifer J. D.; Salathia, Neeraj; et al. (Pigment cell and melanoma research, 2018)
Summary To determine the feasibility of liquid biopsy for monitoring of patients with advanced melanoma, cell‐free DNA was extracted from plasma for 25 Stage III/IV patients, most (84.0%) having received previous therapy. DNA concentrations ranged from 0.6 to 390.0 ng/ml (median = 7.8 ng/ml) and were positively correlated with tumor burden as measured by imaging (Spearman rho = 0.5435, p = .0363). Using ultra‐deep sequencing for a 61‐gene panel, one or more mutations were detected in 12 of 25 samples (48.0%), and this proportion did not vary significantly for patients on or off therapy at the time of blood draw (52.9% and 37.5% respectively; p = .673). Sixteen mutations were detected in eight different genes, with the most frequent mutations detected in BRAF, NRAS, and KIT. Allele fractions ranged from 1.1% to 63.2% (median = 29.1%). Among patients with tissue next‐generation sequencing, nine of 11 plasma mutations were also detected in matched tissue, for a concordance of 81.8%.